Quality of Life in Children With Epilepsy, Evaluated by the Parents on the Basis of Qolce Questionnaire - Felsmann, Mirosława; Futyma, Barbara; Felsmann, Mariusz Zbigniew; Humańska, Marzena Anna; Haor, Beata (Medical and Biological Sciences, 2012)
Epilepsy is a neurological chronic disease, which may negatively influence physical, psychological and social functioning. This problem mainly refers to children with epilepsy in whom, as the research proves, a number of common problems appears, not only those related to epileptic seizures, but also problems connected with cognitive sphere and difficulties at school, as well as social stigma among peers. In the last years, the researches evaluating the quality of life in children with epilepsy have been focused on its complex evaluation. Therefore, adequate measuring tools have been looked for in order to make this evaluation possible. In the research, evaluation of the quality of life was made in a group of 43 children with epilepsy, with the use of QOLCE questionnaire, adapted to Polish conditions by a team directed by K. Mathiak. Most of 16 subscales showed a high and very high reliability according to Cronbach’s α from 0.734 to 0.942. These results point to existence of significant dependence between individual spheres of children’s functioning. In the authors’ opinion, it is worth to compare parents’ evaluation with opinions of children, especially elder ones.